Art Therapy Training in the Preparation of Educator-Psychologists and Social Educators of Al-Farabi Kazakh National University. (Journal of Educational Sciences, 2016)
In modern psychological-pedagogical practice of art therapy is widely used for work with children and adults. In the article discusses functions of art therapy: diagnostic, communicative, regulatory, cognitive, correctional anddevelopmental. The paper considers possibilities of art-therapy and purpose of art-therapeutic work. Development of creative abilities impossible without specially organized psychological-pedagogicalenvironment which participants are immersed in the creative process as in the stream. The described technology of carrying out the master-class on intuitive painting, held for students of specialty «Pedagogic and psychology», «Social educator and self-cognition» of the faculty of philosophy and science of the al-Farabi Kazakh national University. Training of art-therapeutic technology for intuitive painting was tested in the Treasury. The training consisted of three stages: diagnostics, correction and development. Used exercise «the wizard and the duck»,exercises candidate Popes – «Asterisk», «Waterfall of light», «Predictor». This training can be called psychological training on iso-therapy. Students freely wrote their works using all the available materials – paper and canvas, acrylic and watercolor paints, brushes and pencils. Students, on the one hand, and developed their creative abilities, on the other hand, have mastered the art-therapeutic technology.
Keywords: intuitive painting; art-therapy; functions; art therapy; psychological-pedagogical environment